Factors deterring schools from mixed attainment teaching practice - Taylor, Becky; Francis, Becky; Archer, Lousie; Hodgen, Jeremy; Pepper, David; Tereschchenko, Antonina; Travers, Mary-Clare (Taylor & Francis, 2017)
Mixed-attainment teaching has strong support from research and yet English schools are far more likely to teach students in ‘ability’ groups. Although research has considered some of the specific benefits of mixed-attainment grouping, there has been little attention to the reasons schools avoid it. This article explores data from the pilot and recruitment phases of a large-scale study into grouping practices and seeks to identify reasons for the low rate of mixed attainment grouping in English secondary schools. We report on our struggle to recruit schools, and explore the different explanations provided by teachers as to why mixed attainment practice is seen as problematic. The difficulties are characterised as a vicious circle where schools are deterred by a paucity of exemplars and resources and the educational climate is characterised as fearful, risk-averse and time-poor. Suggestions are made as to strategies to support schools in taking up mixed attainment practices.